Role of Anti-Müllerian Hormone in the Central Regulation of Fertility - Cotellessa, Ludovica; Giacobini, Paolo (Seminars in Reproductive Medicine, 2024)
In recent years, the expanding roles of anti-Müllerian hormone (AMH) in various aspects of reproductive health have attracted significant attention. Initially recognized for its classical role in male sexual differentiation, AMH is produced postnatally by the Sertoli cells in the male testes and by the granulosa cells in the female ovaries. Traditionally, it was believed to primarily influence gonadal development and function. However, research over the last decade has unveiled novel actions of AMH beyond the gonads, specifically all along the hypothalamic–pituitary–gonadal axis. This review will focus on the emerging roles of AMH within the hypothalamus and discusses its potential implications in reproductive physiology. Additionally, recent preclinical and clinical studies have suggested that elevated levels of AMH may disrupt the hypothalamic network regulating reproduction, which could contribute to the central pathophysiology of polycystic ovary syndrome. These findings underscore the intricate interplay between AMH and the neuroendocrine system, offering new avenues for understanding the mechanisms underlying fertility and reproductive disorders.
Keywords: AMH; hypothalamus; GnRH; PCOS; infertility